LATERALIZATION OF EPILEPTIFORMIC FOCUSES AND COMPONENTS OF SPIKE-WAVE COMPLEXES IN PATIENTS WITH PREFRONTAL EPILEPSY AND PROBLEM OF FUNCTIONAL HEMISPHERIC ASYMMETRY - V. A. Karlov; V. V. Gnezditskii; L. G. Geibatova (Эпилепсия и пароксизмальные состояния)
The article represents the results of investigation of spike wave complex componen lateralization in patient with prefrontal epilepsy. Meaning of absolutely dominance of left hemispheric localization spike and postspike wave was shown. The problem of hemispheric asymmetry is discussed.